Frictional Behavior of Input Sediments to the Hikurangi Trench, New Zealand. (6th September 2018) - Rabinowitz, H. S.; Savage, H. M.; Skarbek, R. M.; Ikari, M. J.; Carpenter, B. M.; Collettini, C.
Abstract: The Hikurangi subduction zone hosts shallow slow‐slip events, possibly extending to the seafloor. The mechanisms allowing for this behavior are poorly understood but are likely a function of the frictional properties of the downgoing seafloor sediments. We conducted friction experiments at a large range of effective stresses, temperatures, and velocities on incoming sediment to the Hikurangi subduction zone to explore the possible connection of frictional properties to slow‐slip events. These experiments were conducted on multiple apparatuses, allowing us to access a wider range of deformation conditions than is available on any one machine. We find that the material frictionally weakens and becomes less velocity strengthening with increasing effective stress, whereas temperature has only a small effect on both friction and frictional stability. When driven at the plate convergence rate, the sediment exhibits velocity‐weakening behavior. These results imply that the frictional properties of the sediment package subducting at Hikurangi could promote slow‐slip events at the pressures, temperatures, and strain rates expected along the plate boundary thrust up to 10‐km depth without requiring elevated pore fluid pressures. The transition to velocity‐strengthening behavior at faster slip rates could provide a mechanism for limiting unstable slip to slow‐sliding velocities, rather than accommodating deformation through ordinary earthquakes. Key Points: Sediments subducting at the Hikurangi Trench become weaker and less velocity strengthening with increasing depth Sediments exhibit a cutoff velocity of 1 μm/s, possibly explaining the presence of shallow slow slip at the Hikurangi Trench Slow slip at the Hikurangi Trench could result from frictional instability, in addition to factors such as elevated pore fluid pressures